EFFECT OF COOLING ON THERMAL PROPERTIES OF TOMATO (SOLANUM LYCOPERSICUM) - Sutarsi Sutarsi; Iwan Taruna; Jihan Hanun (UNEJ e-Proceeding, 2022)
Cooling is the process of removing heat from food products until the product temperature is between -1 to 8oC. The cooling process aims to inhibit the rate of respiration and microbial growth which is the main cause of spoilage. The decrease in temperature during cooling affects the thermal properties of the material. This study aims to determine the cooling behavior of tomatoes and to examine the effect of cooling on the thermal properties of tomatoes. Fresh tomatoes were stored at temperatures of 5 and 10oC and RH 55, 75 and 85%. The decrease in temperature causes a decrease in the value of thermal properties, thermal conductivity and thermal diffusivity of tomatoes. Keywords: cooling effect, tomato, thermal properties